Diel patterns of total suspended solids, turbidity, and water transparency in a highly turbid, shallow lake (Laguna Chascomús, Argentina) - Lagomarsino, Leonardo (2015)
The effects of external physical forcing variables (solar radiation and winds) on short-term dynamics of total suspended solids (TSS), Chlorophyll- a (Chl-a), turbidity levels, and water transparency were studied during 15 days in a highly turbid, shallow lake (Laguna Chascomu´ s, Argentina). Water samples were taken three times per day (8, 14 and 20 h.). Solar radiation and wind velocity showed a repeatedly bell-shaped diurnal pattern, with significant higher values during morning and afternoon, respectively.TSS and turbidity displayed a general decreasing trend during the sampling period, while water transparency showed the opposite trend. Also Chla displayed a decreasing trend and was closely correlated to TSS levels. We assayed a first-order kinetics model to detrend the series, obtaining the rate of change during the night, morning, and afternoon. We observed higher values on afternoon compared to morning for TSS, Chl-a, and turbidity levels and the opposite pattern for water transparency. We conclude that this pattern may result from a combination of biological activity, as it took place after a period of intense photosynthetic activity, together with resuspension by winds during the afternoon, (windiest time of the day).